Competitive impact of the air ticket levy on the European airline market. (15th November 2018) - Ivaldi, Marc; Toru-Delibaşı, Tuba
Abstract: In tribute to Jules Dupuit, this study analyzes how the innovative financing tax for development has influenced the competition among airline companies and to what extent it affected their sales. To do so, we specify an econometric model where the representative consumer chooses the utility maximizing alternative among the differentiated products offered by the airlines which compete in terms of prices. It is a fairly reasonable and well accepted representation of the competition in the airline industry, assuming that the structure of their networks is given in the short run. The present solidarity tax has increased the average price for the European airlines by only 0.08 % and could increase average prices by 1 % if it were applied to all European airlines. Implemented by all countries it would lead to a 0.17 % increase in Air France prices while the price increase would be 1.05 % for the other airlines in our sample. These numbers compared to the growth rate of the air traffic show that the impact of the solidarity tax would be very small. Overall the air ticket levy applied by all European airlines would not affect significantly the degree of competition among airlines. Highlights: Analysis of how the innovative financing tax for development has influenced the competition among airline companies. Estimation of a differentiated product oligopoly model of the European Airlines Industry. Small impact of the solidarity tax on the degree of competition among airlines.